New records of 20 species of Majoidea and Parthenopoidea (Crustacea: Decapoda) along the Paciflc coast of Mexico - Hendrickx, M E (Universidad de Costa Rica, 1990)
Fifty-eight species of Majoidea havc so far been reported from the Gulf of California, Mexico (Garth 1958, 1960, Hendrickx and van der Heiden 1983, 1984, Hendrickx 1987). Of these, about 21 are inhabitants of the rocky intertidal and shallow subtidal environments;. they are usually captured by hand or with small dredges on or near rocky substrate or in sea-grass beds.